ANALISIS PERBANDINGAN PERFORMANCE PADA FOUR STROKE ENGINE MENGGUNAKAN MULTI-FEEDSTOCK BIODIESEL (MINYAK KELAPA SAWIT, MINYAK IKAN SALMON, EKSTRAK KULIT MANGGIS) DENGAN MULTI- FEEDSTOCK BIODIESEL (MINYAK CASTOR, MINYAK LEMAK SAPI, MINYAK CANOLA) - Wildhan Zaky Arsyada; Aminatus Sa'diyah; Muhammad Shah (Proceedings Conference on Marine Engineering and its Application, 2024)
Petroleum-derived fuel oil (BBM) is the main source of energy The large use of petroleum makes petroleum supplies diminish, this is because petroleum has a very important role in the field of transportation and industry. Biodiesel, as an environmentally friendly alternative, is attracting attention with its increasing trend of use. Although biodiesel has many advantages such as being environmentally friendly and reducing emissions, it also has a negative impact on engine performance. Studies show that biodiesel can affect emission characteristics and engine performance, especially when compared to conventional diesel fuel. Therefore, this study addresses the performance comparison of multi-feedstock fuels, such as (palm oil, salmon oil and mangosteen peel extract) with multi-feedstocks, such as (castor oil, tallow oil and canola oil), blended with HSD (Pertamina dex) to become B20, B35 and B100 fuels. The fuels were tested on a four stroke diesel engine with 1000 watts, 2000 watts and 3000 watts of lamp loading with engine speed variations from 900 rpm to 1000 rpm, providing a deeper understanding of diesel engine performance and efficiency.